English in Nordic universities : ideologies and practices - Hultgren, Anna Kristina; Gregersen, Frans; Thøgersen, Jacob (Amsterdam ; Philadelphia : John Benjamin, 2014)
This volume brings together theoretical perspectives and empirical studies on the ongoing Englishization of Nordic universities. A core objective is to contrast and address the gap between ideological representations of this phenomenon and the ways in which it unfolds in the practices on the ground. The book provides perspectives from five Nordic countries: Iceland, Norway, Denmark, Sweden and Finland, with one chapter from each country focusing on ideologies and another on practices. The book is intended to provide an up-to-date resource on the internationalization and Englishization of Nordic universities for scholars, policy makers and anyone wishing to gain an overview of current issues in the field.
Includes bibliographical references and index.
Keywords: English philology. -- Research. -- Norway; English language. -- Influence on Norwegian; Norwegian language. -- Foreign elements. -- English; Language, Universal; kieli; englannin kieli; yliopistot; kielipolitiikka; kulttuurienvälisyys; globalisaatio; kieli ja kielet; opetus; kielen omaksuminen; Islanti; Norja; Ruotsi; Suomi; Tanska; Pohjoismaat